2019
DOI: 10.1029/2018gl081119
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Models Augment Analyst Decisions for Event Discrimination

Abstract: Long‐term seismic monitoring networks are well positioned to leverage advances in machine learning because of the abundance of labeled training data that curated event catalogs provide. We explore the use of convolutional and recurrent neural networks to accomplish discrimination of explosive and tectonic sources for local distances. Using a 5‐year event catalog generated by the University of Utah Seismograph Stations, we train models to produce automated event labels using 90‐s event spectrograms from three‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…phase onset picking and earthquake detection methods to lower the magnitude detection level (e.g., Ross et al, 2018a;Zhu et al, 2019a;Walter et al, 2020;Mousavi et al, 2020, amongst others); ii.) discriminate between volcanic and tectonic earthquakes (e.g., Esposito et al, 2006) and, in the future, after updating INSTANCE with new data and metadata, discriminate earthquakes and other sources of seismic energy (e.g., sonic booms, quarry blasts, underwater explosions) often felt by the population (e.g., Del Pezzo et al, 2003;Linville et al, 2019); iii.) the rapid and accurate characterization of the earthquake source, distance, depth (e.g., Perol et al, 2018;Trugman and Shearer, 2018;Kriegerowski et al, 2018;Zhang et al, 2020;Lomax et al, 2019;Mousavi and Beroza, 2020;Münchmeyer et al, 2021) and of the ground shaking (e.g., Alavi, 2011;Derras et al, 2012;Derras, 2014;Jozinovic et al, 2020;Münchmeyer et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…phase onset picking and earthquake detection methods to lower the magnitude detection level (e.g., Ross et al, 2018a;Zhu et al, 2019a;Walter et al, 2020;Mousavi et al, 2020, amongst others); ii.) discriminate between volcanic and tectonic earthquakes (e.g., Esposito et al, 2006) and, in the future, after updating INSTANCE with new data and metadata, discriminate earthquakes and other sources of seismic energy (e.g., sonic booms, quarry blasts, underwater explosions) often felt by the population (e.g., Del Pezzo et al, 2003;Linville et al, 2019); iii.) the rapid and accurate characterization of the earthquake source, distance, depth (e.g., Perol et al, 2018;Trugman and Shearer, 2018;Kriegerowski et al, 2018;Zhang et al, 2020;Lomax et al, 2019;Mousavi and Beroza, 2020;Münchmeyer et al, 2021) and of the ground shaking (e.g., Alavi, 2011;Derras et al, 2012;Derras, 2014;Jozinovic et al, 2020;Münchmeyer et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…Buscombe and Carini, ; Buscombe et al ., ; Buscombe and Ritchie, ; Linville et al . ; Luo et al ., ; Jiang et al ., ; Reichstein et al ., ). The basic premise of applications such as these, compared to those of other machine learning subcategories, is that it circumvents the need (and the effort required) to make decisions about what extracted image features are important to a specific task, which tends to make the models both more subjective and more powerful.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is a tool to map relationships through a functional model defined using information extracted from data. Various studies concluded that supervised machine learning can identify subtle seismic waveform variations to classify earthquakes, tremors, landslides, avalanches, and mining explosions (Aguiar & Beroza, 2014; Hammer et al, 2013; Linville et al, 2019; Mousavi et al, 2016; Perol et al, 2018; Ross, Meier, & Hauksson, 2018; Ross, Meier, Hauksson, & Heaton, 2018; Rouet‐Leduc et al, 2019). Correctly labeled data with a diverse mixture of seismic signals and a large enough quantity with respect to the complexity of the classification task and type of employed model are necessary for supervised model training (Bishop, 2006).…”
Section: Introductionmentioning
confidence: 99%